THESIS: THE LEGAL FOUNDATIONS OF COLLECTIVE MANAGEMENT OF INTELLECTUAL PROPERTY RIGHTS IN THE EUROPEAN UNION (International Conference on Educational Discoveries and Humanities, 2025)
This dissertation examines the legal foundations governing the collective management of intellectual property (IP) rights within the European Union (EU), with a focus on copyright and related rights. Collective Management Organizations (CMOs) play a pivotal role in licensing, enforcing, and distributing royalties for IP rights, ensuring fair compensation for creators. The study analyzes key legislative instruments, including the Copyright Directive (2001/29/EC), the Collective Rights Management Directive (2014/26/EU), and the Digital Single Market Directive (2019/790/EU), which collectively form a harmonized framework for CMO operations. By exploring the interplay of EU law, national implementations, and judicial interpretations from the Court of Justice of the European Union (CJEU), this research highlights the principles of governance, transparency, and non-discrimination that underpin collective management. The dissertation also addresses contemporary challenges, such as digitalization, cross-border licensing, and the impact of emerging technologies, which necessitate ongoing regulatory adaptation. Through a comparative analysis of Member State practices and case law, this study evaluates the effectiveness of the EU’s legal framework in balancing the interests of rightsholders, users, and the public. The findings contribute to the discourse on IP rights management, offering recommendations for enhancing the efficiency and equity of CMOs in the digital era.